Recent results from the minos experiment - Weber, A (2008)
MINOS is a long baseline neutrino oscillation experiment. Protons from the Fermilab main injector are used to generate an intense muon neutrino beam, which is directed at the Soudan underground laboratory in Northern Minnesota. The result from two years of running with a total exposure of 2.5 × 10 20 protons on target from the NuMI beam is reported. We made a preliminary measurement by comparing the event rate and energy spectra of charge current muon neutrino interactions in the two detectors, which are 1 and 735 km from the neutrino production target. The data is consistent with νμ to ντ oscillation in the so-called atmospheric parameter range with Δm2 = (2.38+0.20-0.16) * 10-3eV2 and sin2 2θ = 1-0.08. Copyright © 2008, by INFN.